1978
DOI: 10.1111/j.1540-8159.1978.tb03504.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atrial Fibrillation in Man: Studies Following Open Heart Surgery*

Abstract: The nature of localized atrial activation during atrial fibrillation was characterized in 34 patients following open heart surgery. Bipolar atrial electrograms (AEG) recorded in each patient with atrial fibrillation exhibited a myriad of sizes, shapes, polarities, amplitudes, and beat-to-beat intervals. On the basis of the AEG morphology and the nature of its baseline, we have classified the recordings into four Types. Type I was characterized by discrete AEG complexes separated by an isoelectric baseline free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(128 citation statements)
references
References 17 publications
3
125
0
Order By: Relevance
“…5 Slocum et al reported that the power spectrum of human intracardiac fibrillation waves has a discrete peak in the 4-9 Hz band, 6 and in our previous study, we found that the specific spectral characteristics of intracardiac fibrillation waves depended on the duration of AF in patients without organic heart disease. 7 A new method for noninvasive assessment of the human AF cycle length using surface ECG with spectral analysis has been reported.…”
Section: Spectral Analysis Of Afmentioning
confidence: 99%
“…5 Slocum et al reported that the power spectrum of human intracardiac fibrillation waves has a discrete peak in the 4-9 Hz band, 6 and in our previous study, we found that the specific spectral characteristics of intracardiac fibrillation waves depended on the duration of AF in patients without organic heart disease. 7 A new method for noninvasive assessment of the human AF cycle length using surface ECG with spectral analysis has been reported.…”
Section: Spectral Analysis Of Afmentioning
confidence: 99%
“…The size of the left atrium is to date the main parameter to support diagnosis and decisions for treatment options [5,6], although its role in predicting outcome after a cardioversion is discussed controversially [7,8]. Further classifications are based on the averaging of P waves [9,10], on the amplitude of the fibrillatory waves in the surface electrocardiogram (ECG) [11], or on the morphology of the intra-atrial ECG [12]. The number and degree of spatial uniformity of wave fronts was used for a classification into three different AF types [13].…”
Section: Introductionmentioning
confidence: 99%
“…7,8) The hypothesis of Moe could be confirmed in the 1980s both in experimental models and humans by mapping of the atrial activation pattern of AF. 9,10) Multiple wandering wavelets in the atria are the basis of AF. The wavelength of these wavelet is the distance traveled by the depolarization wave during the duration of its refractory period (wavelength=effective refractory period x conduction velocity).…”
Section: Discussionmentioning
confidence: 99%
“…6) Shortening of the effective refractory period or lengthening of intraatrial conduction time result in wavelength shortening which would cause AF to perpetuate, since at least 4-6 wavelets, at the same time, are thought to be essential for AF to be persistent. [7][8][9][10] In both AF and rapid atrial arrhythmias, changes in AERP have been demonstrated both in humans and experimental models. 5,[11][12][13] However, in what way does AF affect intraatrial conduction is controversial.…”
mentioning
confidence: 99%